2020
DOI: 10.1002/ajmg.c.31854
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis for carrier diagnosis in hemophilia A and B in the Mexican population: 25 years of experience

Abstract: Our 25 years of experience in carrier diagnosis of hemophilia A (HA) and B (HB) in Mexican population comprises linkage analysis of intragenic F8/F9 neutral variants along with, in severe HA (SHA), detection of F8 int22h and int1h inversions. In symptomatic carriers (SCs) we explored Lyonization to explain their symtomatology. From a DNA-Bank of 3,000 samples, intragenic restriction fragment length (RFLPs) and short tandem repeats (STRs) of F8/F9 genes were assessed by PCR-PAGE and GeneScan. In SHA patients, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…There is an ongoing debate about whether skewed XCI should be defined as a ratio of ≥80:20 or ≥90:10 ( Fahim et al, 2020 ; González-Ramos et al, 2020 ). In our analysis, we applied the ≥80:20 ratio to define skewed XCI.…”
Section: Discussionmentioning
confidence: 99%
“…There is an ongoing debate about whether skewed XCI should be defined as a ratio of ≥80:20 or ≥90:10 ( Fahim et al, 2020 ; González-Ramos et al, 2020 ). In our analysis, we applied the ≥80:20 ratio to define skewed XCI.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all other pathogenic variants are rare and usually confined to a single-family. [4][5][6][7] Despite the advances in treating HA and increasing life expectancy, there are still challenges in management, most notably the development of inhibitors in a significant proportion of patients. Previous studies have shown that inhibitor development depends on multiple variables including genetic factors.…”
Section: Introductionmentioning
confidence: 99%
“…These issues show the importance of the genetic study on HA patients. [4][5][6][7][8] Iran is a country in the Middle East with a population of more than 80 million; where the prevalence of hemophilia is approximately 14 per 100 000. Although several studies have already been done on the molecular defects causing HA, there is still no comprehensive information about the molecular genetics of HA in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…This study presents valuable phenotypic and genotype information to help develop public health measurements to identify at‐risk individuals and population screening based on risk stratification and appropriate genetic counseling. A comprehensive analysis of genetic studies to detect carriers of hemophilia A and B was performed in the Mexican population (González‐Ramos et al, 2020). This study presents data from 558 independent families with hemophilia A ( n = 1,389) and 74 families with hemophilia B ( n = 320).…”
mentioning
confidence: 99%